Simplifying the digital workflow of facial prostheses manufacturing using a three-dimensional (3D) database: setup, development, and aspects of virtual data validation for reproduction. Issue 3 (July 2019) - Unkovskiy, Alexey; Roehler, Ariadne; Huettig, Fabian; Geis-Gerstorfer, Juergen; Brom, Joern; Keutel, Constanze; Spintzyk, Sebastian
Abstract: Purpose: To set up the digital database (DDB) of various anatomical parts, skin details and retention elements in order to simplify the digital workflow of facial prostheses manufacturing; and to quantify the reproduction of skin wrinkles on the prostheses prototypes with stereolithography (SLA) and direct light processing (DLP) methods. Methods: Two structured light scanners were used to obtain the nasal and auricle forms of 50 probands. Furthermore, the ala nasi and scapha areas were captured with the digital single lens reflex camera and saved in jpeg format. The four magnetic retention elements were remodeled in computer aided design (CAD) software. The 14 test blocks with embossed wrinkles of 0.05–0.8 mm were printed with SLA and DLP methods and afterwards analyzed by means of profilometry and confocal microscopy. Results: The introduced DDB allows for production of customized facial prosthesis and makes it possible to consider the integration of concrete retention elements on the CAD stage, which makes the prosthesis modelling more predictable and efficient. The obtained skin structures can be applied onto the prosthesis surface for customization. The reproduction of wrinkles from 0.1 to 0.8 mm in depth may be associated with the loss of 4.5%–11% of its profile with SLA or DLP respectively. Besides, the reproduction of 0.05 mm wrinkles may be met with up to 40% profile increasement. Conclusions: The utilization of DDB may simplify the digital workflow of facial prostheses manufacturing. The transfer of digitally applied skin wrinkles till the prostheses' prototypes may be associated with deviations from 11 to 40%.